Treatment outcomes of multi-drug resistant tuberculosis patients with or without human immunodeficiency virus co-infection in Africa and Asia: Systematic review and meta-analysis. (June 2022) - Kajogoo, Violet Dismas; Lalashowi, Julieth; Olomi, Willyhelmina; Atim, Mary Gorret; Assefa, Dawit Getachew; Sabi, Issa
Abstract: Background: Treatment outcomes of multidrug resistant tuberculosis (MDRTB) is a challenge, especially in resource limited settings. The aim of this study was to compare whether Human Immune Virus (HIV) has influence on the treatment outcomes of MDRTB among patients in Africa and Asia. Methods: Studies were searched from PubMed, Google scholar, African Journals online, EBSCOhost and CENTRAL from year 2000 until January 2021. The participants in the studies were reported of using MDRTB treatment regimen and also included those with HIV. Studies published before 2000 were excluded. Quality of the review was assessed by AMSTEL 2 criteria. The Mantel- Haenszel random effects method was used for the analysis, with risk ratio (RR) as an effect estimate, with 95% confidence interval and using Stata 14 software. Results: Nine studies were included in the meta-analysis. Treatment success was low in HIV negative participants (RR 0.62, 95% CI 0.58–0.67). However, death was higher in the HIV co-infected participants. (RR 1.35, 95% CI 1.25–1.45). There was no significant difference in treatment failure among patients with or without HIV. (RR 1.08, 95% CI 0.97–1.20). Consistently, no significant difference was found in lost to follow up (LTF) between the two groups (RR 1.07, 95% CI 0.93–1.20). Conclusion: Treatment success was lower for the MDRTB and HIV co-infections. No significant difference has been found on other outcomes like failure and lost to follow up between patients with HIV co-infected and HIV negative group. The study limitations are that we had only 2 studies representing Asia, and this could have affected the outcome of results. There is need for interventions to improve treatment success in the HIV co-infected group. Other: The protocol was registered in International prospective register of systematic reviews (PROSPERO), ID: CRD42021247883. There was no funding for the review. Highlights: Human immunodeficiency virus/AIDS. Multidrug-resistant tuberculosis. MDR-TB and HIV co-infection. Treatment outcomes.